Implementación de un sistema automático de Fitomonitoreo Utilizando sensores IoT para la plantación de cacao del proyecto FIASA de la Universidad Técnica de Cotopaxi Extensión La Maná - Basilio Molina, Jhon Cristhian (2023)
This project involves agriculture 4.0 within the agro-productive sectors and the La Maná canton provides agricultural products such as Cocoa, a key plantation where the focus is on collecting data through IoT sensors to carry out data collection in the field that They will allow the agronomist to correlate agroclimatic variables with the development of the plantation. The development of the project was carried out at the Sasha Wiwa experimental center, where the Technical University of Cotopaxi carries out agricultural practices. To strengthen the processes through the use of technology, humidity and temperature sensors for both the environment and the soil were planted, as well as sensors for the levels of rainfall incidence, wind speed and direction, solar radiation and leaf humidity. ECOWITT line, which are connected by radio frequency to a Gateway that serves as a receiver and gateway to send the collected data to a web server that allows the end user to view the data in real time from any mobile device connected to the Internet. and that you have the credentials. Additionally, for the transition from the Internet to the devices, it was decided to install line-of-sight antennas which served to bring connectivity to the terrain where the sensors are incorporated.